ТЕХНОЛОГІЯ СИТУАЦІЙНОГО МЕНЕДЖМЕНТУ ТА ФАКТОРИ, ЩО НА НЕЇ ВПЛИВАЮТЬ - Бойда, Світлана (КНЕУ, 2024)
The relevance of the situational approach to management in the modern conditions of transcendence is investigated and substantiated; the essence and characteristics of situational management are revealed; the factors of favorable and unfavorable influence on the management of Ukrainian enterprises are determined; promising opportunities for domestic business are highlighted.
SITUATIONAL MANAGEMENT TECHNOLOGY AND FACTORS, THAT INFLUENCE IT
Keywords: situational management; management technology; factors of influence; situations; transcendental conditions